Realize Tolerant Students Through Strengthening the Profile of Pancasila Students with Global Diversity in Elementary Schools - Faizah, Silviana Nur; Dina, Lia Nur Atiqoh Bela; Anggraini, Ade Eka (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Cultural awareness enables individuals to behave following social norms in various cultures. This research describes the practice of character cultivation by strengthening the Pancasila Berkebinekaan global student profile project at SDN Pagentan 3, focusing on recognizing and appreciating cultural diversity. A qualitative descriptive method was employed, utilizing data collection techniques such as interviews, observations, and documentation. The findings indicate that cultivating character through the Pancasila Berkebinekaan global student profile project at SDN Pagentan 3 is centered around introducing and understanding values through traditional Indonesian dances, Indonesian cuisine, and traditional attire. This character cultivation involves three stages: 1) the moral knowing stage, achieved through the integration of the curriculum and global diversity values from relevant sources such as images and videos; 2) the moral feeling stage, where students are directly engaged in experiences such as sharing Indonesian cuisine, participating in traditional dances, and wearing traditional attire to foster pride in Indonesian culture and respect for cultural differences. 3) the moral action stage is fostered through activities encouraging students to express their opinions, collaborate, and acknowledge one another's achievements. This research is a reference for educators in designing character education programs to help students internalize global diversity values at the Elementary School level.